2021
DOI: 10.1186/s12920-021-00920-3
|View full text |Cite
|
Sign up to set email alerts
|

A de novo frameshift variant of ANKRD11 (c.1366_1367dup) in a Chinese patient with KBG syndrome

Abstract: Background KBG syndrome is a rare autosomal dominant genetic disease mainly caused by pathogenic variants of ankyrin repeat domain-containing protein 11 (ANKRD11) or deletions involving ANKRD11. Herein, we report a novel de novo heterozygous frameshift ANKRD11 variant via whole exome sequencing in a Chinese girl with KBG syndrome. Case presentation A 2-year-2-month-old girl presented with a short stature and developmental delay. Comprehensive physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Gnazzo et al (2020) reported a 13% prevalence of strabismus, whereas Choi et al (2023) reported a single case of strabismus among their cohort. Chen et al (2021) and Nizette and Duchesne, (2021) both reported isolated cases of patients with KBG syndrome having binocular refractive errors, with the latter also reporting concurrent bilateral corneal clouding. Finally, Novara et al (2017) reported four cases of astigmatism and two cases of myopia among their cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gnazzo et al (2020) reported a 13% prevalence of strabismus, whereas Choi et al (2023) reported a single case of strabismus among their cohort. Chen et al (2021) and Nizette and Duchesne, (2021) both reported isolated cases of patients with KBG syndrome having binocular refractive errors, with the latter also reporting concurrent bilateral corneal clouding. Finally, Novara et al (2017) reported four cases of astigmatism and two cases of myopia among their cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Although ophthalmological findings have been reported in some cases of KBG syndrome (Brancati et al, 2006; Chen et al, 2021; Nizette & Duchesne, 2021; Novara et al, 2017), there is currently a lack of research that estimates the incidence of visual problems among those with diagnosed KBG syndrome, or determines if there is a link between KBG syndrome and visual impairments. Our analysis of visual impairments in patients with KBG syndrome hints that a significant relationship may exist between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Although ophthalmological findings have been reported in some cases of KBG syndrome [2,11,17,18], there is currently a lack of research that estimates the incidence of visual problems among those with diagnosed KBG syndrome, or determines if there is a link between KBG syndrome and visual impairments. Our analysis of visual impairments in patients with KBG syndrome hints that a significant relationship may exist between the two.…”
Section: -Discussionmentioning
confidence: 99%
“…All SEMDs are characterized by short stature. However, ID is only observed in some patients with SEMDs, including DMC, Faden-Alkuraya type (RSPRY1 variant) [Faden et al, 2015], Liberfarb type (PISD) [Girisha et al, 2019;Zhao et al, 2019], Camera-Genevieve type (NANS) [Geneviève et al, 2005;van Karnebeek et al, 2016], Krakow type (SIK3) [Csukasi et al, 2018], KBG syndrome (ANKRD11) [Chen et al, 2021], and SEMD-HL (AIFM1) [Miyake et al, 2017]. Patients with DMC have unusual features such as coarse face, microcephaly, and lacy appearance in the iliac crests on radiography.…”
Section: Discussionmentioning
confidence: 99%